1999
DOI: 10.3354/dao036077
|View full text |Cite
|
Sign up to set email alerts
|

Description of a hepatopancreatic rickettsia-like organism in the redclaw crayfish Cherax quadricarinatus

Abstract: ABSTRACT. Basovhilic, Gram-neaative, nucrocolonies of rick- Rickettsia-like organisms (RLO) infect a range of aquahc crustaceans mcludmg amphpods, crabs, prawns and freshwater crayfish (Federici et al. 1974, Bonami & Pappalardo 1980, Johnson 1984, Sparks et al. 1985, Brock et al. 1986, Anderson et al. 1987, Krol et al. 1991, Ketterer et al. 1992, Owens et al. 1992, Bower et al. 1996. The decapod-infecting RLOs are either confined to the hepatopancreatic tubule epithelium, or are systemic. The systemic RLOs nev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 7 publications
2
20
0
Order By: Relevance
“…At least two prokaryotic rickettsia-like organisms have been reported to infected freshwater crayfish (KETTERER et al, 1992;OWENS et al, 1992;JIMÉNEZ and ROMERO, 1997;EDGERTON and PRIOR, 1999). One of the RLOs is known to cause serious disease in Cherax quadricarinatus in farms.…”
Section: Bacteriamentioning
confidence: 99%
“…At least two prokaryotic rickettsia-like organisms have been reported to infected freshwater crayfish (KETTERER et al, 1992;OWENS et al, 1992;JIMÉNEZ and ROMERO, 1997;EDGERTON and PRIOR, 1999). One of the RLOs is known to cause serious disease in Cherax quadricarinatus in farms.…”
Section: Bacteriamentioning
confidence: 99%
“…Similarly, Edgerton et al (1995) found the presence of 2 species of rickettsiae, 1 in the cytoplasm of hepatopancreatic cells (Edgerton & Prior 1999) with mortalities up to 80% in several farms (Jimenez & Romero 1997). The bacteria exhibited morphology and characteristics similar to those reported by Edgerton et al (1995).…”
Section: Introductionmentioning
confidence: 99%
“…To survive and reproduce, the rickettsia organism must enter the eucaryotic host cell, multiply within the cell, exit and reestablish this cycle in another cell (Winkler 1990). Rickettsia-like microorganisms infect a wide range of aquatic crustaceans including amphipods, crabs, freshwater crayfish and prawns (Federici et al 1974, Harshbarger et al 1977, Bonami & Pappalardo 1980, Larrson 1982, Johnson 1984, Brock et al 1986, Anderson et al 1987, Krol et al 1991, Frelier et al 1992, Fryer & Lan-nan 1994, Bower et al 1996, Jimenez & Romero 1997, Edgerton & Prior 1999, Wang & Gu 2002.…”
Section: Introductionmentioning
confidence: 99%